Between “Improvisation” and “a Poem Yet to Be Written”: A Cross-Reading of Gli immediati dintorni and Il musicante di Saint-Merry (inOpera Esercizi di lettura su testi contemporanei, 2025)
This study analyzes the structural and translational choices in Vittorio Sereni’s Il musicante di Saint-Merry, probing its connections with the prose collection Gli immediati dintorni. Disavowing theoretical systematization – a stance particularly apt for Sereni’s resistant poetics – this essay adopts a lateral approach. It prioritizes the why over the how of translational decisions that trace what might be termed a “parallel diary”, while mapping the intertextual echoes between the two works. Ultimately, it aims to illuminate that liminal space where memory and revision, mediation and rewriting converge—the very locus of these texts’ textual “truth”.
Keywords: Vittorio Sereni; Poetry-prose dialogue; Diary as Discourse; Translational Strategies; Intertextual